Modeling of orthogonality factor using ray-tracing predictions. - Passerini, C. (IEEE Transactions on wireless communications)
This paper presents an analysis of the results obtained simulating the orthogonality factor (OF) in an urban microcellular channel. This paper is focused on two main issues: the reliability of ray-tracing (RT) simulations when predicting the OF and the modeling of the OF over a global and a local area. This paper presents a novel approach to the assessment of the accuracy and robustness of RT channel estimates, and specifically of the OF. It shows that the expected accuracy in estimating the OF is comparable to the accuracy in estimating the narrow-band channel losses and that the estimation is robust: thus it is suggested that simulations can be used to extract empirical models of the OF. This paper presents two models derived from a large number of simulations: one is for the coverage area and the other is for local fluctuations. These models can effectively be used in simulations of the static or the dynamic performance of third-generation mobile systems.